The Ngorongoro Crater as the biggest geotouristic attraction of the Gregory Rift (Northern Tanzania, Africa) – geographical setting - Żaba, Jerzy; Gaidzik, Krzysztof (Geotourism/Geoturystyka, 2025)
The caldera of an extinct Ngorongoro volcano is the largest unflooded and not destroyed type of this form on Earth. The depression itself occupies an area of nearly 300 km2, while the Crater walls tower a few hundred metres (400–610 m) above the floor of the caldera. Almost all typical for East Africa plants and animals, as well as rare, endemic and often endangered species can be observed in the crater. The unique richness and diversity of natural world of the Ngorongoro Crater is caused exceptionally by favourable weather and hydrological conditions. These factors depend on local conditions, associated with significant relief of this area. Probably, the most important is the richness of the Ngorongoro Crater in water. There occur springs, perennial and seasonal rivers, marshes, swamps, as well as reservoirs of fresh and salty water. Essential is also the presence of the local autochthonous population of the Maasai people, which raises the attractiveness of that localization adding so important cultural values. Due to its unique natural and touristic values, the Ngorongoro Conservation Area (NCA) has been established in 1959. The area was also included into the UNESCO World Cultural and Natural Heritage List. This paper presents only the geographical setting of the Ngorongoro Crater, which should be understood as its morphology, hydrological and climatic conditions, wildlife and indigenous local people.